2017
DOI: 10.1186/s12942-016-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer: density equalizing mapping of the global research architecture

Abstract: BackgroundDespite its impact on female health worldwide, no efforts have been made to depict the global architecture of ovarian cancer research and to understand the trends in the related literature. Hence, it was the objective of this study to assess the global scientific performance chronologically, geographically and in regards to economic benchmarks using bibliometric tools and density equalizing map projections.MethodsThe NewQIS platform was employed to identify all ovarian cancer related articles publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 55 publications
(56 reference statements)
3
31
0
Order By: Relevance
“…Furthermore, most of the social networking sites were established and founded in the USA. These findings are similar to those found in previous bibliometric studies in different fields, principally that the USA had the highest activity in scientific research output worldwide and in international collaboration networks, as well as the highest h-index [32,[35][36][37]. Regarding the international collaboration, this emphasizes the significance of global networking and its impact on research output [38][39][40][41].…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, most of the social networking sites were established and founded in the USA. These findings are similar to those found in previous bibliometric studies in different fields, principally that the USA had the highest activity in scientific research output worldwide and in international collaboration networks, as well as the highest h-index [32,[35][36][37]. Regarding the international collaboration, this emphasizes the significance of global networking and its impact on research output [38][39][40][41].…”
Section: Resultssupporting
confidence: 90%
“…Ovarian cancer (OC) is the most common malignancy in women, and its incidence is increasing worldwide [1]. Despite the development of surgery and adjuvant therapies, the overall prognosis of patients with OC remains poor, especially in those with advanced stage disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…China-a rising star in many areas of science-does also appear in some NewQIS assessments prominently as shown for ovarian cancer research in Fig. 3c (Bruggmann et al 2017d). Concerning Asian countries, a previous assessment of 5527,558 articles has indicated that Asian countries have largely different research focuses in comparison to Western countries (Groneberg-Kloft et al 2008b).…”
Section: Visualizationmentioning
confidence: 84%
“…c DEMP exemplifying prominent Chinese research activities in ovarian cancer research. Data fromBruggmann et al (2017d)…”
mentioning
confidence: 99%